Butch/Femme in the personal advertisements of lesbians - Smith, Christine A.; Stillman, Shannon (Journal of Lesbian Studies, 2002)
Personal advertisements placed by lesbians were examined to determine how often butch/femme descriptors were used: (a) as a form of self-identification or (b) to indicate the type of partner being sought. The 388 personal advertisements were drawn from 16 alternative newspapers around the U.S., as well as from one Internet site (Qworld) that contained personal ads by lesbians. Each advertisement was coded for the presence or absence of butch/femme descriptors. The majority of advertisers did not mention butch or femme labels either in terms of self-identity or type of partner sought. Among the minority of advertisers who self-identified as butch or femme, more described themselves as femme than butch. Among advertisers seeking butch or femme partners, femme partners were sought most often. Explanations for the preference for femme lesbians were explored
Keywords: amériques; butch/femme; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines; états-unis